Third world military expenditure : determinants and implications - McKinlay, Robert D. (Bloomsbury academic collections. History and politics in the 20th century : postcolonialsim., 2016)
"The twin objectives of this book are to identity the determinants and to explore the implications of Third World military expenditure. Beginning with a descriptive profile of Third World military expenditure, the study uses cross-national and longitudinal data to explore the determinants and implications across a range of issues areas. On the basis of this analysis, the book concludes with an empirical theory of military expenditure and a critical appraisal of the general implications."--Bloomsbury Publishing